Fulbright-Hays Seminars Abroad Program Malaysia 1995. Participants' Reports. (Distributed by ERIC Clearinghouse, 1995)
These reports and lesson plans were developed by teachers and coordinators who traveled to Malaysia during the summer of 1995 as part of the U.S. Department of Education's Fulbright-Hays Seminars Abroad Program. Sections of the report include: (1) "Gender and Economics: Malaysia" (Mary C. Furlong); (2) "Malaysia: An Integrated, Interdisciplinary Social Studies Unit for Middle School/High School Students" (Nancy K. Hof); (3) "Malaysian Adventure: The Cultural Diversity of Malaysia" (Genevieve M. Homiller); (4) "Celebrating Cultural Diversity: The Traditional Malay Marriage Ritual" (Dorene H. James); (5) "An Introduction of Malaysia: A Mini-unit for Sixth Graders" (John F. Kennedy); (6) "Malaysia: An Interdisciplinary Unit in English Literature and Social Studies" (Carol M. Krause); (7) "Malaysia and the Challenge of Development by the Year 2020" (Neale McGoldrick); (8) "The Iban: From Sea Pirates to Dwellers of the Rain Forest" (Margaret E. Oriol); (9) "Vision 2020" (Louis R. Price); (10) "Sarawak for Sale: A Simulation of Environmental Decision Making in Malaysia" (Kathleen L. Prout); (11) "Malaysia: A Model Unit for Study of a Contemporary Culture" (Virginia K. Roll); (12) "Present Day Primary Education of the Pribumi Sea-Dayaks in the Second Division of Sarawak, Malaysia (Barry G. Sprague); and (13) "Vision 2020" (Risa E. Weinberger). Many units also include bibliographies and additional resources. (CB)
ERIC Document Number: ED405265.
ERIC Note: Some images will not reproduce clearly.
Also distributed on microfiche by U.S. GPO under ED 1.310/2:405265.
Keywords: Area Studies.; Asian History.; Asian Studies.; Cultural Background.; Culture.; Elementary Secondary Education.; Foreign Countries.; Foreign Culture.; Global Education.; Human Geography.; Instructional Materials.; Non Western Civilization.; Social Studies.; World Geography.; World History.